Rapid detection of Rotavirus antigen in stool sample of acute diarrheic children - Roy, Sushmita; Shamsuzzaman, S.M.; Mamun, K.Z. (Bangladesh Journal of Medical Microbiology, 2012)
Rotavirus is one of the leading causes of pediatric diarrhea globally. Accurate and rapid diagnosis of Rotavirus diarrhea should reduce unnecessary use of antibiotics and ultimately reduce drug resistance. Study was designed for rapid diagnosis of Rotavirus antigen in stool sample by ICT (Immunochromatographic test) as well as to observe the seasonal variation of rotavirus infection. This cross sectional study was carried out in the department of Microbiology, Dhaka Medical College from January 2011 to December 2011. Eighty stool samples were collected from Dhaka Shishu Hospital and Dhaka Medical College Hospital. All samples were tested for rotavirus antigen by ICT. Among 80 patients, 42 (52.5%) samples were positive for rotavirus antigen. Among these 42 positive samples, 30 (71.43%) were from 0-12 months of age group, 10 (23.81%) from 13 to 24 months of age group and rest 2 (4.76%) from 25 to 36 months of age group. Rotavirus Ag was detected in stool samples from January to April and another peak episode from October to December. Considering the importance of Rotavirus associated diarrhea, rapid detection of Rotavirus infection in human is substantially needed and should be routinely practiced. DOI: http://dx.doi.org/10.3329/bjmm.v6i1.19354 Bangladesh J Med Microbiol 2012; 06(01): 11-13